METODE PENETAPAN WAKTU SALAT MENURUT DEWAN SYARIAH WAHDAH ISLAMIYAH - Ronny Mahmuddin; Abdul Munawir; Muslimin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aimed to identify and recognize the correct method in determining shari prayer times according to Sharia Board of Wahdah Islamiyah. The issues in this study were; First, Islamic jurisprudence and the position of the sun being the main point of reference according to the Sharia in determining the initial time for prayer; Second, the law of employing astronomy in determining the initial time for prayer; Third, the correct method in determining shari prayer times according to Sharia Board of Wahdah Islamiyah. The type used was descriptive qualitative (non-statistical) research, which focused on the study of scripts and texts, employing a normative approach (shari) with field studies in the form of interviews with related figures. The results of the study show that; first, to recognize the Islamic jurisprudence and the position of the sun as the main point of reference in determining the initial time for prayer must be understood based on the propositions in the Koran and sunnah through the interpretation of the scholars who were well-known for their credibility. Second, in determining the prayer time schedule, the main method used is the method of rukyat with the help of astronomy as a means and device, but not as a primary point of reference. In addition, the process of preparing the prayer schedule is necessarily conducted through discussions by experts of Islamic jurisprudence and astronomy, both those affiliated with Wahdah Islamiyah and experts from outside Wahdah Islamiyah who are willing to provide recommendations and suggestions.